The effect of atazanavir and atazanavir/ritonavir on UDP-glucuronosyltransferase using lamotrigine as a phenotypic probe - Burger, D M; Huisman, A; Van Ewijk, N; Neisingh, H; Van Uden, P; Rongen, G A; Koopmans, P; Bertz, R J (Clinical pharmacology and therapeutics, 2008)
Atazanavir (ATV) is known to inhibit UGT1A1-mediated glucuronidation. Here we report the effect of ATV and ATV/ritonavir (RTV) on another UGT1A isoenzyme, UGT1A4. Twenty-one healthy volunteers received a single dose of 100 mg of oral lamotrigine on days 1, 13, and 27; on each occasion blood was sampled before the dose was administered and through 120 h after ingestion of the drug. On days 8-17 the subjects received oral ATV 400 mg q.d. On days 18-30 the subjects received oral ATV 300 mg plus oral RTV 100 mg q.d. Seventeen subjects were evaluable for pharmacokinetic analysis. Geometric mean ratios (+90% confidence intervals (CIs)) of lamotrigine area under the plasma concentration-time curve (AUC)(0-inf) and peak plasma concentration (C(max)) for ATV + lamotrigine and for lamotrigine alone were 0.88 (0.86-0.91) and 0.99 (0.95-1.02), respectively; the corresponding ratios for ATV/RTV and for lamotrigine were 0.68 (0.65-0.70) and 0.94 (0.90-0.97), respectively. The mean ratio of lamotrigine-2N-glucuronide to lamotrigine AUC(0-inf) increased from 0.45 for lamotrigine to 0.71 for ATV/RTV + lamotrigine. ATV alone does not significantly influence glucuronidation of lamotrigine. In contrast, ATV/RTV results in moderately decreased exposure to lamotrigine.